Prevalence and Mortality of Hypochloremia Among Patients Suffering From Coronary Artery Disease and Congestive Heart Failure: An Analysis of Patients in CIN-I and MIMIC-III Databases - Huang, Haozhang; Liu, Jin; Liang, Yan; Bao, Kunming; Qiao, Linfang; Liu, Jiulin; Li, Qiang; Wang, Bo; Chen, Shiqun; Lai, Wenguang; Chen, Cong; Zhang, Lingyu; et al. (Frontiers in Medicine, 2021)
Background Hypochloremia is an independent predictor for mortality in patients with coronary artery disease (CAD) but whether the same correlation exists in CAD patients with congestive heart failure (CHF) is unclear. Methods This is an analysis of data stored in the databases of the CIN-I [a registry of Cardiorenal Improvement (NCT04407936) in China from January 2007 to December 2018] and Medical Information Mart for Intensive Care (MIMIC)-III. CAD patients with CHF were included. Ninety-day all-cause mortality (ACM) and long-term ACM were the outcome measures. Results Data from 8,243 CAD patients with CHF were analyzed. We found that 10.2% of the study population had hypochloremia (Cl− < 98 mmol/L) in CIN-I (n = 4,762) and 20.1% had hypochloremia in MIMIC-III (n=3,481). Patients suffering from hypochloremia were, in general, older and had a higher prevalence of comorbidities. After adjustment for confounders, hypochloremia remained a significant predictor of short-term mortality risk [90-day ACM: adjusted hazard ratio (aHR), 1.69; 95% confidence interval (CI), 1.27–2.25; P < 0.001 in CIN-I, and 1.36 (1.17–1.59); P < 0.001 in MIMIC-III]. Hypochloremia was also associated with long-term mortality [aHR, 1.26; 95%CI, 1.06–1.50; P = 0.009 in CIN-I, and 1.48 (1.32–1.66); P < 0.001 in MIMIC-III]. Prespecified subgroup analyses revealed an association of hypochloremia with long-term ACM to be attenuated slightly in the females of the two databases (P interaction < 0.05). Conclusions Hypochloremia is independently associated with higher short-term and long-term ACM. Further studies are needed to determine if early preventive measurements and active intervention of hypochloremia can reduce the mortality risk of CAD patients with CHF.